New Frontiers in Entrepreneurial Finance Research - Quas, Anita; Alperovych, Yan; Bellavitis, Cristiano; Paeleman, Ine; Kamuriwo, Dzidziso Samuel (Singapore:World Scientific, 2019)
Ten papers consider new sources of entrepreneurial finance, highlighting angel investors, government interventions, financial technology innovations, and how entrepreneurs' characteristics relate to fundraising success. Papers discuss the role of angel syndicates on the demand and supply of informal venture capital (VC); government intervention in VC markets; the validity of guarantee instruments; green project crowdfunding; linguistic style approaches for gaining empathetic attention from crowdfunding investors; blockchain, cryptocurrency, and initial coin offerings; the development of the minibond market for small and medium-sized enterprises; facilitating access to early-stage equity financing in developing countries; the financial literacy of entrepreneurs; and the pedagogical value of social entrepreneurship competitions at the individual level. Quas is Senior Researcher in Corporate Finance at Universita degli Studi di Milano. Alperovych is Associate Professor of Corporate Finance at EMLYON Business School. Bellavitis is Lecturer of Innovation and Entrepreneurship in the Faculty of Management and International Business of Auckland Business School at the University of Auckland. Paeleman is Assistant Professor at the University of Antwerp. Kamuriwo is Associate Professor in Strategy in the Cass Business School at City, University of London. Index.